1-Year pullout strength and degradation of ultrasound welded vs tapped craniomaxillofacial fixation screws. (May 2022) - López, Alejandro; Ayyachi, Thayanithi; Brouwers, Tessa; Åberg, Jonas; Wistrand, Anna Finne; Engqvist, Håkan
Abstract: A knowledge on the pullout forces of degradable craniomaxillofacial screws is essential in designing pediatric cranial implants. Herein, four non-identical commercially available screws composed of different aliphatic polyesters were fixated to 3D-printed poly(l -lactide) screw hole test rig and onto a bone substitute material using manual tapping and ultrasonic welding fixation techniques. A method for mechanical testing was developed to determine and compare their quasi-static pullout strength. The degradation of the screws was followed for up to one year in three different degrading environments. While the screw size influences the initial pullout force, the degrading environment, size, and screw composition determine the degradation rate which in turn influences the pullout force over time. Given the limited availability of standard methods, the method developed herein can be used in determining the pullout forces of degradable craniomaxillofacial screws and comparing the effectiveness of various screw insertion techniques. Highlights: A method to measure the pullout force of degradable craniomaxillofacial screws have been developed Three long-term degradation setups were designed to evaluate the in vitro screw degradation The major determinant of pullout force of the screws is their contact surface area with the bone substituent material The reduction of pullout forces depends on the levels of polymer degradation.